Parent Management Training untuk Meningkatkan Keterampilan Sosial Anak yang Mengalami Oppsitional Defiant Disoder - Yulia Hairina; Amitya Kumara; Uly Gusniarti (Universitas Islam Indonesia, 2010)
This study aimed to determine if whether the parent management training can improve social skills in children experienced oppositional defiant disorder (ODD). Subjects in the study one child, oppositional defiant disorder (ODD), male gender, age 7 years, currently sit in second grade elementary school. The data was collected using the method of observation with anecdotal records and behavioral checklists and semi-structured interviews. The study design used was a single case experimental design with AB-follow up design. Analysis of the data used is a qualitative analysis with the analysis of behavioral approaches RAC-S (Response, Antecendents, Consequences, Response-Strength), and analysis visual inspection. The results of parent management training can improve social skills of child who has oppositional defiant disorder, primarily on behavioral aspect of academic success in school.Keywords: Social Skills, Parent Management Training, Oppositional Defiant Disorder